Virome analysis of field-collected chilli samples reveals diverse viruses - Vamsidhar Reddy Netla; Shridhar Hiremath; Mantesh Muttappagol; H. D. Vinay Kumar; S. Koti Prasanna; T. L. Mohan Kumar; C. R. Jahir Basha; V. Venkataravanappa; K. S. Shankarappa; M. N. Maruthi; C. N. Lakshminarayana Reddy (Virology Journal)
Abstract Background Chilli (Capsicum annuum L.), an important spice crop, is susceptible to diverse viral infections. Traditional detection methods including PCR and its variants had difficulty in identifying the complete spectrum of viruses, especially in mixed infections. High-throughput sequencing (HTS) has emerged as a successful tool for comprehensive virome analyses, enabling the identification of the known and novel viruses in the infected samples. Using HTS, we investigated virome analyses to identify known and novel viruses in chilli. Methods In 2021–22, 19 leaf samples were collected from chili plants in farmer fields in Karnataka, India, showing symptoms such as leaf curling, vein banding, mosaic, mottling, filiform, leathery, dull-colored, and bunchy leaves. Total RNA was extracted, pooled at equimolar concentrations, and subjected to virome profiling. rRNA-depleted RNA was used to prepare mRNA and sRNA libraries, which were sequenced on the Illumina NovaSeq 6000 platform. Bioinformatics tools were used to analyze the sequencing data and identify plant viruses. Results Viral disease incidences varied from 26.6 to 47.5% in the farmer fields surveyed. Virome analyses revealed complete/ near-complete genomes of six different viruses: chilli leaf curl virus (ChiLCV), cucumber mosaic virus (CMV), groundnut bud necrosis orthotospovirus (GBNV), pepper cryptic virus-2 (PCV-2), pepper vein yellows virus (PeVYV) and bell pepper alphaendornavirus (BPEV). The viral copy number of ChiLCV was found to be the highest (45.36%) and had the least mutational frequency (SNPs) and was also associated with five satellites. Recombination breakpoints were observed in ChiLCV (coat protein and AC4 regions), CMV RNA2 (2a protein) and PeVYV (P0, P3 and P5 proteins), indicating their origins from intra- and interspecific recombination events. Identified viruses in the pooled RNA sample were confirmed by PCR. Further, novel loop-mediated isothermal amplification (LAMP) diagnostic assays were developed for diagnosing the identified viruses for future use. Among the six viruses identified in chilli, PeVYV and BPEV are the first reports from India. Conclusions This study presents the first virome profiling of chili using HTS and identified known and previously unreported viruses in farmer fields of Karnataka, India. Understanding viral diversity provides insights for developing diagnostic tools and effective management strategies.